Office-based Needle Arthroscopy for the Foot and Ankle. Issue 1 (March 2015) - Labib, Sameh A.; Slone, Harris S.
Abstract : The authors present their early experience with an office-based needle arthroscopy performed under local anesthesia to diagnose intra-articular pathology in the foot. The technique is described with indications, contraindications, risks, and benefits of the procedure.Level of Evidence: Diagnostic Level 5. See Instructions for Authors for a complete description of levels of evidence.